A Digital Platform for a Multichannel Digital Wideband Scanning Receiver - Langmann, Frank; Mzyk, Raphael; Dehm-Andone, Gunther; Fischer, Georg; Weigel, Robert (7th Karlsruhe Workshop on Software Radios, 2012)
elib2cris::1512001600,hausknecht2012
Keywords: Digital; Platform; Multichannel; Scanning; Receiver; Architecture

A multichannel scanning receiver system for surveillance applications - Hausknecht, Frank; Mzyk, Raphael; Dehm-Andone, Gunther; Fischer, Georg; Weigel, Robert (6th Future Security Research conference, 2011)
elib2cris::1512001600,hausknecht2011
Keywords: Multichannel; scanning; Receiver; surveillance

Analysis of Key Modules in an Analog Front-End for Scanning Receiver Systems - Mzyk, Raphael; Dehm-Andone, Gunther; Langmann, Frank; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (IEEE International Conference on Microwaves, Radar & Wireless Communications, 2012)
In this paper, a cost-effective approach on receiver systems for frequency scanning and direction finding applications is presented. A hybrid approach on analog front-end topology is introduced, that combines direct sampling and double superheterodyne architecture. Key modules like a reconfigurable filter, reference clock distribution units, and low noise PLL (phaselocked loop) are highlighted and the trade-off between cost effectiveness and performance is investigated. The performance of those modules is presented by measurement results.
elib2cris::1512001600,mzyk2012a
Keywords: Scanning receiver; surveillance; clock distribution; frequency synthesis; reconfigurable filter

Design Aspects of Scanning Receiver Systems - Mzyk, Raphael; Dehm-Andone, Gunther; Langmann, Frank; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (IEEE German Microwave Conference, 2012)
In this paper, a cost-effective approach on receiver systems for frequency scanning and direction finding applications is presented. It consists of a hybrid analog topology, combining direct sampling and double superheterodyne architecture, as well as a scalable digital platform that offers multi channel data aquisition requiring minimum hardware ressources. The receiver front-end covers the VHF (very high frequency) and UHF (ultra high frequency) band from 30MHz to 3GHz while a 50MHz instantaneous bandwidth can be processed. Key modules like a reconfigurable filter and low noise PLL (phase-locked loop) as well as a digital platform are highlighted and the trade-off between cost effectiveness and performance is investigated.
elib2cris::1512001600,mzyk2012
Keywords: Scanning receiver; frequency synthesis; reconfigurable filter; multi channel receiver

Discussion on Receiver Topologies in the Context of Intelligence Applications - Mzyk, Raphael; Dehm-Andone, Gunther; Hausknecht, Frank (Electrical and Electronic Engineering for Communication, 2011)
elib2cris::1512001600,mzyk2011
Keywords: scanning receiver; Intelligence; receiver topologies; KAIMAN

Efficient Firmware Implementation of a Multichannel Scanning Receiver for Surveillance Applications - Langmann, Frank; Mzyk, Raphael; Dehm-Andone, Gunther; Trautwein, Uwe; Fischer, Georg; Weigel, Robert (IEEE International Conference on Communication and Signal Processing 2012, 2012)
elib2cris::1512001600,hausknecht2012a
Keywords: Scanning; Surveillance; Receiver; Firmware; Digital; Multichannel

Entwurf und Realisierung einer mehrkanaligen ZF-Ethernet-Umsetzerarchitektur zur schnellen Funkaufklärung - Langmann, Frank (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)

Evaluierung eines Verfahrens zur Positionsbestimmung von Funkemittern fuer ein gegebenes Empfaengersystem - Hausknecht, Frank; Wibbing, Sascha (Radio Techniques and Technologies for Commercial Communication and Sensing Applications, 2011)
elib2cris::1512001600,hausknecht2011a

Filter Design Aspects in Analog Receiver Front-Ends for Frequency Scanning Applications - Dehm-Andone, Gunther; Mzyk, Raphael; Langmann, Frank; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (International Symposium on Signals, Systems and Electronics 2012, 2012)
In this paper, the design of filter components for a frequency scanning receiver RF front-end is described. The front-end is an integral component of a multichannel scanning and DF (direction finding) system. It covers a broad frequency range of VHF (very high frequency) and UHF (ultra high frequency) from 30MHz to 3GHz and comprises a scalable multichannel digital receiver as well as a hybrid synchronizable double superheterodyne analog receiver approach with direct sampling path. Focus is put on optimizing cost and benefit by balancing system and filter design efforts and choosing efficient technologies for filter implementation using COTS (commercial off-the-shelf) components. The design and implementation of a reconfigurable preselection filter bank, a coupled line resonator IF (intermediate frequency) filter, and a COTS IF filter bank are presented. The performance of these modules is demonstrated by measurement and simulation results.
elib2cris::1512001600,dehm-andone2012
Keywords: Front-End; Filter design; RF; Filter bank; IF filter; Design aspects